Enantiopure bicyclic piperidinones: stereoselectivity in lactam enolate alkylations. - Brewster, A; Broady, S; Davies, C; Heightman, T; Hermitage, SA; Hughes, M; Moloney, M; Woods, G (2004)
The synthesis and alkylation of [4.3.0]-bicyclic lactams, derived from 6-oxopipecolic acid, have been investigated. Alkylation can proceed with predominantly exo-diastereoselectivity, but the efficiency of this process depends on the substitution at the hemiaminal ether system. These products can be readily deprotected to give substituted hydroxymethyl lactams in good yield.